The Influence of Nonaudit Service Revenues and Client Pressure on External Auditors' Decisions to Rely on Internal Audit* - FELIX, WILLIAM L.; GRAMLING, AUDREY A.; MALETTA, MARIO J. (Contemporary Accounting Research, 2005)
Abstract This paper investigates how external auditor provision of significant nonaudit services and client pressure to use the work of internal audit influence external auditors' use of internal auditors' work. More specifically, we study how external audit evidence gathering choices are influenced by nonaudit fees and client pressure. Our research is motivated by an observation that the magnitude of nonaudit services provided to audit clients introduces the risk that client management may leverage its position with the external auditor and potentially affect the audit process. We address this issue by extending prior research and focusing on the importance of various explanatory variables, including nonaudit service revenues, client pressure, internal audit quality, and coordination, to the external auditor's decision to rely on the work of internal audit. We use data primarily obtained through surveys completed by internal and external auditors. The survey responses represent 74 separate audit engagements. Our findings reveal that when significant nonaudit services are not provided to a client, internal audit quality and the level of internal‐external auditor coordination positively affect auditors' internal audit reliance decisions. However, when the auditor provides significant nonaudit services to the client, internal audit quality and the extent of internal ‐ external auditor coordination do not significantly affect auditors' reliance decisions. Furthermore, when significant nonaudit services are provided, client pressure significantly increases the extent of internal audit reliance. Thus, external auditors appear to be more affected by client pressure and less concerned about internal audit quality and coordination when making internal audit reliance decisions at clients for whom significant nonaudit services are also provided.